There is a sign problem when iev(A,B) is defined. You mention that you can get the mutual information of A and B by taking -log_2 of probabilistic evidence pev(A,B) = P(AB) / [P(A)P(B)], but this creates an extra negative sign:
-log_2(pev(A,B)) = -log_2[P(AB) / [P(A)P(B)]] = -[ log_2(P(AB)) - [log_2(P(A)) + log_2(P(B))] ] = -log_2(P(AB)) + log_2(P(A)) + log_2(P(B)) = inf(AB) - inf(A) - inf(B).
There is a sign problem when iev(A,B) is defined. You mention that you can get the mutual information of A and B by taking -log_2 of probabilistic evidence pev(A,B) = P(AB) / [P(A)P(B)], but this creates an extra negative sign:
-log_2(pev(A,B)) = -log_2[P(AB) / [P(A)P(B)]] = -[ log_2(P(AB)) - [log_2(P(A)) + log_2(P(B))] ] = -log_2(P(AB)) + log_2(P(A)) + log_2(P(B)) = inf(AB) - inf(A) - inf(B).